2022
DOI: 10.3390/healthcare10050872
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Predictive Index for Type 2 Diabetes Mellitus Patients Based on Biological, Social, Housing Environment, and Psychological Well-Being Factors

Abstract: Indonesia is currently undergoing an epidemiological transition, with the double burden of disease due to increasing industrialization and urbanization leading to an increase in the prevalence of non-communicable diseases such as obesity and diabetes. On the other hand, the prevalence of infectious diseases such as tuberculosis remains high. Several factors were considered as risk factors in tuberculosis coincidence with type 2 diabetes mellitus. The purpose of this study was to develop a predictive index for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, the results showed that there is no obvious spatial heterogeneity in the four risk factors (age, hypertension, dyslipidemia, and smoking history). This might be because this study did not incorporate socioeconomic and environmental factors into the study [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results showed that there is no obvious spatial heterogeneity in the four risk factors (age, hypertension, dyslipidemia, and smoking history). This might be because this study did not incorporate socioeconomic and environmental factors into the study [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pleiotropy test assesses whether multiple instrumental variables exhibit horizontal pleiotropy, commonly indicated by the intercept term in MR-Egger regression. A significant deviation of the intercept term from zero suggests the presence of horizontal pleiotropy [ 16 ]. The leave-one-out sensitivity test calculates the MR result with one instrumental variable excluded at a time [ 17 ].…”
Section: Methodsmentioning
confidence: 99%